Achieving global surgical excellence: an evidence-based framework to guide surgical quality improvement programs in low and middle income countries - Henry, Jaymie Claire; Wong, Lye-Yeng; Reyes, Ana M.; Jin, James Z.; Ferguson, Mark K.; Yip, Cheng Har; Hill, Andrew (Frontiers in Health Services, 2023)
Objectives: There is a lack of evidence-based guidelines for enhancing global surgical care delivery. We propose a set of recommendations to serve as a framework to guide surgical quality improvement and scale-up initiatives in low and middle income countries (LMICs). Methods: From January-December 2019, we reviewed the available literature and their application toward LMIC settings. The first initiative was the establishment of Best Practices Recommendations intended to summarize best-level evidence around quality improvement processes that have shown to decrease morbidity and mortality in LMICs. The GRADE level of evidence and strength of the recommendation were assigned in accordance with the WHO handbook for guidelines development. The second initiative was the scale-up of principles and practices by establishing international expert consensus on the optimal organization of surgical services in LMICs using a modified Delphi methodology. Results: Recommendations for three topic areas were established: reducing surgical site infections, improving quality of trauma systems, and interventions to reduce maternal and perinatal mortality. 27 studies were included in a quantitative synthesis and meta-analysis for interventions reducing surgical site infections, 27 studies for interventions improving the quality of trauma systems, and 14 studies for interventions reducing maternal and perinatal mortality. Using Delphi methodology, an international expert panel established consensus that district hospitals should place the highest priority on developing surgical services for low complexity, high volume conditions. At the national level, emergency and essential surgical care should be integrated within national Universal Health Coverage frameworks. Conclusions This project fills a critical cap in the rapidly developing field of global surgery: gathering evidence-based, practical, and cost-effective solutions that will serve as a guide for the efficient planning and allocation of resources necessary to promote quality and safe essential surgical services in LMICs.